Understanding the Dorsal and Ventral Systems of the Human Cerebral Cortex. - Borst, Grégoire; Thompson, William L.; Kosslyn, Stephen M. (American Psychologist, 2011)
Traditionally, characterizations of the macrolevel functional organization of the human cerebral cortex have focused on the left and right cerebral hemispheres. However, the idea of left brain versus right brain functions has been shown to be an oversimplification. We argue here that a top-bottom divide, rather than a left-right divide, is a more fruitful way to organize human cortical brain functions. However, current characterizations of the functions of the dorsal (top) and ventral (bottom) systems have rested on dichotomies, namely where versus what and how versus what. We propose that characterizing information-processing systems leads to a better macrolevel organization of cortical function; specifically, we hypothesize that the dorsal system is driven by expectations and processes sequences, relations, and movement, whereas the ventral system categorizes stimuli in parallel, focuses on individual events, and processes object properties (such as shape in vision and pitch in audition). To test this hypothesis, we reviewed over 100 relevant studies in the human neuroinzaging and neuropsychological literatures and coded them relative to 11 variables, some of which characterized our hypothesis and some of which characterized the previous dichotomies. The results of forward stepwise logistic regressions supported our characterization of the 2 systems and showed that this model predicted the empirical fundings better than either the traditional dichotomies or a left-right difference. Reprinted by permission of the publisher.